Interferensi antara bahasa arab Dengan bahasa madura (Studi Kasus Pada Mahasiswa Prodi Pendidikan Bahasa Arab STAI Syaichona Moh. Cholil Bangkalan - Humaidi . (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2019)
In the aspect of social life, the function of language is traditionally as a verbal medium and also as a communication tool to convey thoughts of ideas and concepts, If in a society it consists of various regions with different language uses, language contacts and language interference will arisebetween the first language and the second language, that's why the researchers chose the title of interference that occurs between the languages first language (Madurans language) with the second language (Arabic language). In this research there are two formulations of the problem studied, the first is how is the form of interference used by students of syaichona cholil state, the second is how to speak the correct pronunciation of Arabic after interference. The formulation are intended to find out the various forms of interference that are often used and to provide knowledge on how to pronounce the correct language.This research uses descriptive qualitative research with the method of collecting data through three types, interviews, observation, and documentation with using the miles analysis model.The results of this research concluded that the occurrence of phonological and morphological interference was categorized into three typesfirst, elemental interference,interference is which occurs because of the inclusion of the morphological elements of the Madurans language into Arabic-like morphology, affixesthe example of the word astaghfirullah becomes poralla and syaitan becomes satan and others. Second, the interference pattern is morphological interference in the form of the use of the Madura language morphological process patterns in the formation of Arabic words the example of la ba’tsa( لابأس ) becomes la madza madza (لا ماذا ماذا. )Third, combination interference is the occurrence of elemental interference and interference patterns in one sentence like the word قلب قلب (be careful).